THE EFFECT OF SERVICE QUALITY, PATIENT RELATIONSHIP MANAGEMENT AND SERVICE FAIRNESS ON LOYALTY THROUGH PATIENT SATISFACTION OF TYPE B HOSPITALS IN DKI JAKARTA - Rudianto, Setiawan Eko; Sayidah, Nur; Riyadi, Slamet; Marwiyah, Siti; Sukesi; Assagaf, Aminullah; Tampubolon, Liosten R. R. Ully; Albab, Eric Ulul (Antis-Publisher, 2026)
Objective: This study aims to (1) examine the influence of service quality, patient relationship management, and service fairness on patient satisfaction and loyalty, and (2) test whether patient satisfaction mediates the influence of service quality, patient relationship management, and service fairness on patient loyalty. Method: A quantitative approach was employed with a survey conducted on 320 respondents, consisting of inpatients in several hospitals in DKI Jakarta, and the data were analyzed using linear regression analysis and mediation tests. Result: The findings of this study are: (1) the quality of service has no effect on patient satisfaction and loyalty; (2) patient relationship management has no effect on patient satisfaction but has a positive effect on patient loyalty; (3) service fairness has a positive effect on patient satisfaction and loyalty; (4) patient satisfaction has no effect on patient loyalty; (5) patient satisfaction is not an intervening variable between service quality and patient relationship management to patient loyalty; and (6) patient satisfaction is an intervening variable between service fairness and patient loyalty. Novelty: The results show that service justice has a great influence on both patient satisfaction and loyalty, proving that the variable of service justice in which there are indicators of retributive justice is a proven novelty, highlighting the importance of leaders in formulating policies related to fairness in service and ensuring the implementation of fair services by all hospital employees to increase satisfaction and ultimately foster patient loyalty.